Experience Quality: A Hybrid Systematic Literature Review and Bibliometric Analysis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Although Experience Quality has been extensively researched, comprehensive studies remain limited. This research aims to conduct a Systematic Literature Review (SLR) and bibliometric analysis of existing empirical work on Experience Quality. The methodology used is SLR, with data collected from the Scopus database using the search term